Plan de negocio para la creación de un centro terapéutico de biomagnetismo, cantón La Maná, año 2014. - Abril Cócheres, Diana Gabriela (2015)
present study has as main objective to establish the costs and expenses to determine the feasibility of the business plan for the creation of a therapeutic center of biomagnetism in the canton The Manna, year 2014. The therapeutic center of biomagnetism has as purpose to offer an alternative diversification of therapies guided to the physical, mental and emotional health, to offer a service of quality through responsible and qualified personnel, with competitive prices and considering the economic situation of the inhabitants of the canton The Manna. The business will be constituted with the name of April Center CORP., under the denomination of anonymous company that will allow the reception of future interested investors. The market study demonstrates us that 89,9% of those interviewed accepts the idea of the business plan considering this percentage it is obtained that the demand belongs to 16.973 clients, you necessary that the year the therapeutic center offers its services to 11.450 clients so that it doesn't exist lost, considering an estimate in the price, each service will have a cost of $12,50, for each therapy through the technical study you stable that the business this located in the Av. May 19 among Eugenio Mirror being a strategic point for the reception of clients. The evaluation index shows that TIR of the project reaches 31,96%, overcoming the interest rate of 20,84%, demonstrating that the business is feasible, he/she also manifests us that you to recover the investment in the first year of operation.